INFLUENCE OF EXPOSURE TO FACEBOOK ON SELF-ESTEEM - Omolayo, Benjamin O.; Balogun, Shyngle K.; Omole, Olajumoke C. (European Scientific Journal, ESJ, 2013)
The study examines the influence that activities on Facebook have on self-esteem. It aims at finding whether Facebook activities will increase or decrease users’ self-esteem. 192 students selected from two universities participated in the study and their age ranges between 16 to 35 years. Data were collected with the use of two standardized research instruments namely Facebook Intensity Questionnaire (FBI) and Rosenberg Self-Esteem Scale (RSE). The data were analyzed using t-test for independent groups and One-way Analysis of Variance (ANOVA). Four hypotheses were tested and results show a significant positive influence of Facebook on self-esteem. Age was found to have significant influence on self-esteem but not on Facebook usage. Also, no significant difference exists between female and male usage of Facebook. Findings also indicated that using headphones for Facebooking does not bring about greater self-esteem over those using desktop and laptop computers for Facebooking. It was concluded that engaging in Facebook activities will positively influence the self-esteem of Facebook users.